Environmental performance of alternative end-of-life scenarios for electrical and electronic equipment: A case study for vacuum cleaners. (15th August 2017) - Pérez-Belis, Victoria; Bakker, Conny; Juan, Pablo; Bovea, María D.
Abstract: Extending the product life span of electrical and electronic equipment is considered an optimal strategy for resource conservation as consuming new resources to produce new appliances is avoided, and the amount of generated waste is reduced. However with energy-using products, the energy efficiency of equipment and other user-related behaviour variables play a key role when determining the best end-of-life scenario from an environmental viewpoint. This research aimed to identify the optimal replacement time by considering two main situations from an environmental perspective. In Situation 1 (equipment does not need repairing during its life span), two scenarios are compared: using equipment until the end of its life span versus replacing it with more energy-efficient equipment. In Situation 2 (equipment breaks and needs repairing during its life span), two scenarios are compared: repairing equipment and using it until the end of its life span versus not repairing and replacing it with more energy-efficient equipment. To this end, the life cycle assessment methodology is applied. The definition of the life cycle of each scenario combines the energy class of the initial appliance and the energy class of the replacing one, as well as their years of use. Apart from this, different consumer use behaviours are also considered, based on the equipment's frequency of use. Finally according to an analysis of main failures, different repair requirements are also considered in each scenario. The results, after taking a domestic vacuum cleaner as the case study, show that consumer use behaviour is the variable that most affects the environmental impact when selecting the scenario with less environmental impact for each situation. According to the consumer profile, for consumers who use vacuum cleaners occasionally, using and repairing (if required) them until the end of their life span is the most recommendable option. However, for other consumer use behaviours (those who vacuum often), replacement with a more energy-efficient vacuum cleaner is recommendable when the difference between the initial and the replacing energy efficiency class of vacuum cleaner exceeds two levels. Highlights: Factors affecting the end-of-life of electrical and electronic equipment are identified. A methodology based on a comparison of different end-of-life scenarios for electrical and electronic equipment is proposed. Aspects such as energy efficiency, life span, years of use, consumer behaviour and type of repair are considered.